THE ANALYSIS OF INSTAGRAM USERS AMONG STUDENTS OF SMA NEGERI 1 PERCUT SEI TUAN - Yolanda, Esy Putri; Zuhriah, Zuhriah (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the patterns of use, motivations, and the positive and negative impacts of Instagram on students at SMA Negeri 1 Percut Sei Tuan. Employing a qualitative approach, data were collected through in-depth interviews with five students who actively use Instagram. The results indicate that Instagram is accessed almost daily, particularly during leisure time at home or school breaks. The most frequently used features include Stories, Reels, and Direct Messages (DM). The primary motivations for using Instagram are entertainment, information seeking, and self-expression. Socially, Instagram has a positive effect by helping students maintain friendships and express their identities. However, it also poses negative impacts, such as disrupting concentration and causing social pressure through self-comparison. Therefore, it is crucial for adolescents to manage their time effectively and use social media responsibly.